Investigating the behavior of silicon-coated Kevlar fabric under low-velocity impact: An experimental and numerical study. (May 2019) - Abbaszadeh, A; Yazdani, M; Abbasi, F; Rashed, A
This study reports experimental and numerical behaviors of both dry and silicon-coated twill-weave Kevlar fabrics under low-velocity impact. Initially, the fabrics are augmented in silicon aqueous suspension with various particle concentrations, and then, increase in the weight and friction coefficient are studied. The low-velocity impact test results show that the best particle concentration to meet the mentioned requirements is about 10 wt%. The experiments indicate high-impact resistance of the target by increase in the number of fabric plies. It is found that silicon-coated fabrics under drop-weight test show more time duration of impact and better performance than dry fabrics. Furthermore, the tests show that in the dry fabrics, broader region stretches due to impact, while in silicon-coated fabrics, the damage is limited to the impact point. The numerical simulation is performed for the coated fabric, and the effect of fabric augmentation with silicon is introduced as yarn friction. The numerical results are in good agreement with the experimental results.